2020
DOI: 10.1080/13102818.2020.1749528
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gamma-decalactone biosynthesis by yeast Yarrowia lipolytica MTLY40-2p and W29 in batch-cultures

Abstract: Gamma-decalactone is an interesting flavuring compound with an intense oily-peachy aroma. It is commonly used in food and cosmetic industry. Biotechnological methods of its synthesis are based on the processes of fatty acid degradation, mainly ricinoleic acid, which is the main component of castor oil. The aim of this study was to compare the productivity of gamma-decalactone in batch cultures of two strains of Yarrowia lipolytica, wild strain W29 and its derived mutant MTLY40-2p, grown in flasks and a bioreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The detected fermentation by-products included 2(5H)-furanone as a flavor component, γ-decalactone as an aromatic compound, and benzaldehyde as a volatile flavor compound. γ-Decalactone was synthesized by yeast Yarrowia lipolytica through oxidative degradation of fatty acids [29]. A similar metabolic process yields γdecalactone in kombucha through the activity of the bacterium Acetobacter indonesiensis [30].…”
Section: Chemical Compound Profiling Of Extract and Fermented Extractmentioning
confidence: 99%
“…The detected fermentation by-products included 2(5H)-furanone as a flavor component, γ-decalactone as an aromatic compound, and benzaldehyde as a volatile flavor compound. γ-Decalactone was synthesized by yeast Yarrowia lipolytica through oxidative degradation of fatty acids [29]. A similar metabolic process yields γdecalactone in kombucha through the activity of the bacterium Acetobacter indonesiensis [30].…”
Section: Chemical Compound Profiling Of Extract and Fermented Extractmentioning
confidence: 99%
“…γdecalactone is the most interesting of these and the one with the most focus in the literature. It is described as pleasantly oily-peachlike (Braga and Belo, 2016;Małajowicz et al, 2020). It has been found that the main component of castor oil, ricinoleic acid, a C18hydroxylated fatty acid, is one of the most promising substrates for optimised production of γ-decalactone (Braga and Belo, 2013;Braga and Belo, 2015;Braga and Belo, 2016;Małajowicz et al, 2020;Kothari et al, 2022).…”
Section: The Potential Of Y Lipolytica For Producing Pleasant and Fun...mentioning
confidence: 99%
“…It is described as pleasantly oily-peachlike (Braga and Belo, 2016;Małajowicz et al, 2020). It has been found that the main component of castor oil, ricinoleic acid, a C18hydroxylated fatty acid, is one of the most promising substrates for optimised production of γ-decalactone (Braga and Belo, 2013;Braga and Belo, 2015;Braga and Belo, 2016;Małajowicz et al, 2020;Kothari et al, 2022). More than 400 fatty acids are found in milk, with the diversity originating from which animal it is derived from and what feed is given (Barłowska and Litwińczuk, 2009;Markiewicz-Kęszycka et al, 2013;Djordjevic et al, 2019).…”
Section: The Potential Of Y Lipolytica For Producing Pleasant and Fun...mentioning
confidence: 99%
“…Gamma-decalactone (GDL), a kind of safe natural aroma compound with an oily-peachy-like flavor, 1,2 is in great demand in the field of foods, pharmaceuticals, and cosmetics. Traditionally, natural GDL mainly relies on plant extraction which is severely restricted by region and season, and its market price is extremely high (US$ 6000 kg −1 , about 40 times that of chemical synthetic products) with a problem of insufficient market supply.…”
Section: Introductionmentioning
confidence: 99%
“…Usually substrates used for biotransformation are ricinoleic acid (RA), castor oil and ricinic acid methyl ester (RAME), which is based on the biotransformation mechanism of degradation of fatty acid. 2 As a result, the substrate, used in the process of biotransformation to prepare GDL, is a fat-soluble substance. The biotransformation is carried out in oil-water phase system which automatically generate emulsifier and form a homogeneous emulsion system ultimately.…”
Section: Introductionmentioning
confidence: 99%